The Power of TikTok in Influencing MSME Consumer Impulse Buying Behavior - Aloysius Rangga Aditya Nalendra; slamet Heri Winarno; Agus Priadi (University of Merdeka Malang, 2026)
This study examines the influence of Social Media Marketing, Electronic Word of Mouth (E-WOM), and Flash Sale on Impulse Buying, with Perceived Value as a mediating variable, among consumers of micro, small, and medium enterprises (MSMEs) on TikTok. A quantitative approach was adopted, drawing on survey data from 196 active TikTok users residing in North Bekasi who had purchased MSME products via TikTok Shop or the live-streaming feature. Respondents were selected via purposive sampling, and the sample size was determined using the Lemeshow formula. The findings demonstrate that Social Media Marketing, E-WOM, and Flash Sale each exert a positive and significant effect on both Perceived Value and Impulse Buying. Perceived Value, in turn, significantly predicts Impulse Buying and fully mediates the relationship between the three marketing stimuli and impulsive purchase behavior. These results indicate that TikTok-based digital marketing strategies can meaningfully enhance consumers' perceived value and, consequently, stimulate impulse buying for MSME products. Theoretical and managerial implications are discussed in the context of social commerce and MSME digital transformation.